Mental health in a municipality in the State of Parana from a subjective perspective (Research, Society and Development, 2020)
Considering the high index of research in mental health, psychiatrist and psychologist, this study is based on a survey carried out with the number of referrals in mental health in 2018, in the Guaíra city, in the State of Paraná. Trying to discuss the life complexity of the person who seeks this service from a subjective point of view, and as a perspective to treat the dynamics of this person who is affected by mental behavior, deconstructing the traditional biomedical model based on the disease. It is understood that the person must be considered in his/her uniqueness, however the environment in which he/she lives, his/her Family, social and affective relationships have a significant impact on his/her life and are constructed throughout his/her development process, in a practical and singular. Through a quantitative field research, it was obtained as a result, it was found that the total mean age of the sample was 30.5 (SD= 20.3) males and 37.7 (SD= 18.2) females. Representing 71.5% females and 28.4% males, which indicates the highest referral rates for these specialties in adult women (31 – 40 years) and in men the largest number is in Young people and adolescents (11- 20 years). There was also a significant number of Young women and adolescents (17.4%), the second highest referral rate. According to the authors who deals with this subject matter and this survey, women are more prone to depression and anxiety, and mental impairment may be linked to a traumatic situation in its childhood, such as violence and education, extending into adult life through frustrations.